Body, Beauty, and Death in an Andean Context: A Self-Ethnographic Narration - Segovia, Jimena Silva (Qualitative Sociology Review, 2020)
With this article I seek to build bridges between the different narrative elements where the body is situated as a central language, of experiences as a researcher in socio-cultural contexts of Bolivian indigenous peoples in the years 1984 and 1998. In this biographical period I have lived different reflective processes, frustrations, and successes that can contribute to an understanding of the framework of gender, ethnic, and political relations. This text, auto-ethnographic, enables us to see the deconstruction and subjective transformations in an androcentric context of a traditional Andean culture, as well as the investigative awareness achieved during interactions in the field. In my field work I have used tools from different disciplines (anthropology, sociology, social psychology), that are useful for validating the autoethnography as a methodological model to the gender autonomy, listening and learning the different ways of understanding corporal discourses. That is, I wish to recognize the value of various types of production and interpretation of knowledge, such as narration, arts, literature, film, and photography that favors emancipation of the peoples and their inhabitants.